Inovasi Pembelajaran Bahasa Inggris: Penggunaan Media Phonemic Chart Untuk Meningkatkan Pemahaman Bunyi Vokal Pada Siswa SMA 2 Indrajaya - Nurjannah; Iqbal; Farizawati; Zuhra, Intan; Zulkifli; Nurfadillah (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2025)
Phonology and phonetics are fundamental areas of language study, particularly for language learners aiming to acquire accurate pronunciation. The use of the phonemic chart has become a powerful tool in teaching these concepts, as it visually represents the sounds of a language. This training was hold at SMA N 2 INDRAJAYA. The numbers of participant were 35 students. It aims to improve the student ability in producing the monophthongs. They were active and enthusiasm during this training. The result showed that the students were able to produce some monopthongs words such as sound [ə] di kata banana, [æ]dikata cat, [ɒ] dikata pot. This training really helped the students in improving their ability in improving the vowel sounds. For next section, this training should be held for the other sounds.